KEMAMPUAN PREDIKSI TERHADAP PENDAPATAN DAN ARUS KAS OPERASIONAL LANCAR UNTUK ARUS KAS OPERASIONAL MASA DEPAN - Aliamin -; Jen Surya (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2008)
The aim of this research is to investigate ability prediction of earnings and current operating cash flows to future operating cash flows, the profit report use  are  firms  reporting  positive  profit  and  firms  reporting  negative  profit. There are several  prior study indicates a strengthening relationship between earnings and future operating cash flows for both firms profit reporting and losses reporting, while relationship between current and future operating cash flows are neither increasing nor decreasing. The result of research indicates that both earnings and cash flows have ability to predict future operating cash flow for positive profit reporting. On the other hand, negative profit reporting, earnings are not significant to predict future operating cash flows while current operating cash flows still have ability to predict future operating cash flows.  Key words:   earnings, current operating cash flows, future operating cash flows, positive profit reporting, negative profit reporting